Heat and Mass Transfer Effect on Steady MHD Flow through an Isothermal Vertical Porous Surface - Moheswari, P. (Asian Review of Mechanical Engineering, 2017)
Magneto hydro dynamic effects of heat and mass transfer on continuously moving isothermal vertical porous surface is investigated. The boundary layer equations are transformed into ordinary differential equations. The Velocity, temperature and concentration profiles are studied for different non dimensional parameters like thermal Grashof number, mass Grashof number, Schmidt number, Prandtl number, porosity parameter and Hartmann number. The results are discussed with the help of graphs.